The role of plasminogen activator inhibitor 1 (PAI-1) after menopause – the influence of hormonal therapy of this period - Stachowiak, Grzegorz; Stetkiewicz, Tomasz; Połać, Ireneusz; Sobczuk, Anna; Jędrzejczyk, Sławomir; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
PAI-1 is an important inhibitor in the fibrinolytic system. In this article the connection of this glycoprotein with cardiovascular system, obesity and neoplasms in the group of postmenopausal women has been presented. Increased PAI-1 levels after menopause testify to the impaired fibrinolysis, unfavourably influencing female health status. Whereas estrogens, being administered at this time, advantageously decrease its level, enhancing fibrinolytic potential of serum.